Optimizing 3-Axis CNC Router Design: Using QFD and DFM for Enhanced Precision and Efficiency - Mohammad Rivo Firgiawan; Yunia Dwie Nurcahyanie (bit-Tech, 2025)
The development of the manufacturing industry demands continuous innovation in machine technology, particularly the 3 Axis CNC Router, which plays a crucial role in various applications such as cutting, milling, and material shaping.This research aims to design and develop a more efficient and precise 3 Axis CNC Router machine with a user needs-based approach in Indonesia.This machine is optimized using Quality Function Deployment (QFD) to identify consumer needs through questionnaire data, as well as Design for Manufacture (DFM) to ensure a design that is easy to produce and cost-efficient.The results of the QFD and DFM analysis are used to develop the machine with superior features, such as improved cutting precision, reduced noise, and enhanced resistance to corrosion and material dust accumulation. The developed machine is capable of improving cutting accuracy to ±0.05 mm and processing speed by 20% faster compared to the previous machine.Additionally, the noise reduction also reaches more than 15 dB, enhancing operator comfort during use.This research also identifies the main customer needs, such as machine safety, speed, and machine strength, as well as secondary needs, such as aesthetics and dirt prevention.These findings not only provide technical solutions to the existing issues with CNC machines but also suggest a direction for developing machines that are more responsive to the needs of small and medium-sized enterprises in Indonesia, as well as more efficient in material and cost usage.